2000
DOI: 10.1074/jbc.275.1.571
|View full text |Cite
|
Sign up to set email alerts
|

Coregulator Small Nuclear RING Finger Protein (SNURF) Enhances Sp1- and Steroid Receptor-mediated Transcription by Different Mechanisms

Abstract: The small nuclear RING finger protein SNURF is not only a coactivator in steroid receptor-dependent transcription but also activates transcription from steroidindependent promoters. In this work, we show that SNURF, via the RING finger domain, enhances protein binding to Sp1 elements/GC boxes and interacts and cooperates with Sp1 in transcriptional activation. The activation of androgen receptor (AR) function requires regions other than the RING finger of SNURF, and SNURF does not influence binding of AR to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 59 publications
2
63
0
Order By: Relevance
“…In addition, RNF4 is a transcriptional coregulator for members of the nuclear receptor superfamily that are sumoylated within their transcriptional inhibitory domains (Moilanen et al, 1998;Poukka et al, 2000b;AbdelHafiz et al, 2002;Tian et al, 2002). Interestingly, the residues of RNF4 that are required for its interaction with the androgen receptor (amino acids 31-65 (Poukka et al, 2000a)) encompass the SIMs that we identified. Furthermore, the SUMO and ubiquitin-dependent regulation of D. discoideum MEK1, an MAP kinase kinase required for chemotaxis, provides particularly compelling support for our model (Sobko et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RNF4 is a transcriptional coregulator for members of the nuclear receptor superfamily that are sumoylated within their transcriptional inhibitory domains (Moilanen et al, 1998;Poukka et al, 2000b;AbdelHafiz et al, 2002;Tian et al, 2002). Interestingly, the residues of RNF4 that are required for its interaction with the androgen receptor (amino acids 31-65 (Poukka et al, 2000a)) encompass the SIMs that we identified. Furthermore, the SUMO and ubiquitin-dependent regulation of D. discoideum MEK1, an MAP kinase kinase required for chemotaxis, provides particularly compelling support for our model (Sobko et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…RNF4 can interact with both DNA and proteins (transcription factors) and may promote an assembly of nucleoprotein structures (12). It has been shown that RNF4 modulates the transcriptional activities of androgen receptor and SP1 via different domains, and it may act as a functional link between steroidand SP1-regulated transcription (16). Moreover, it has been shown that RNF4 facilitates AR import to nuclei and retards its export on hormone withdrawal, suggesting that RNF4-me- diated tethering of AR in nuclei represents a novel mechanism for activating steroid receptor functions (27).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which RNF4 modulates androgen-dependent transcription have been investigated (12,14,16,26). RNF4 can interact with both DNA and proteins (transcription factors) and may promote an assembly of nucleoprotein structures (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the PEST sequence in the AR hinge region overlaps the bipartite nuclear translocation region (19,26), it is possible that ubiquitination of AR in this region may provide the recognition site for proteasome association, resulting in the modulation of AR nuclear translocation. To support the role of the ubiquitin-proteasome pathway in AR nuclear translocation, it has been shown that the Snurf1 coregulator, a RING finger protein, could bind to the AR hinge region to enhance AR transactivation via promotion of AR nuclear translocation (19,42). However, it remains to be determined whether Snurf1 has intrinsic E3 ligase activity to ubiquitinate AR and allow proteasome recognition and thus promotion of AR nuclear translocation.…”
Section: Mg132 Inhibits the Interaction Between Ar And Ar Coregulators-mentioning
confidence: 99%